Efficacy, Immunogenicity and Safety of COVID-19 Vaccines: A Systematic Review and Meta-Analysis - Sharif, Nadim; Alzahrani, Khalid J.; Ahmed, Shamsun Nahar; Dey, Shuvra Kanti (Frontiers in Immunology, 2021)
There is a significant research gap on meta-analysis on the efficacy and safety of coronavrus disease 2019 (COVID-19) vaccines. This study analyzed the efficacy of COVID-19 vaccines. This study included published trials of phase-I, phase-II and phase-III for analyzing safety and immunogenicity and randomized clinical trials of phase-III for evaluating efficacy of COVID-19 vaccines. We searched Medline, Scopus and The Lancet for published articles evaluating the relative reduction in COVID-19 risk after vaccination. Selected literatures were published between December 15, 2019 to May 15, 2021 on safety, efficacy and immunogenicity of COVID-19 vaccines. This meta-analysis included studies that confirmed the cases of COVID-19 by reverse transcriptase polymerase chain reaction. This study detected 8926 eligible research articles published on COVID-19 vaccines. Of these research articles, 25 studies fulfilled inclusion criteria. Among the selected articles, 19 randomized clinical trials, 2 non-randomized clinical trials and 3 observational studies were analyzed. Seven (28%) studies were included in the meta-analysis. Efficacy of adenovirus vector vaccine was 73% [95% CI, 69-77] and mRNA vaccine was 85% [95% CI, 82-88] in participants aged ≥18 years. No study reported clinical trials in participants aged below 16 years. Production of neutralizing antibodies against receptor binding domains (RBD) of SARS-CoV-2 in >90% of the vaccinated samples were reported within 0-30 days of first or second dose of vaccination. Pain at injection site was the most common local symptom in people receiving mRNA vaccines (29%-85% participants). Fever (0.2%-95%) was most prevalent in people receiving adenovirus vector vaccines and fatigue (8.4%-55%) was most common in people receiving mRNA vaccines. Studies suggest that mRNA vaccines and adenovirus vector vaccines can provide moderate to high protection against COVID-19 infection in people aged above 18 years. Evidences of long-time protection of vaccines in people aged below 16 years against multiple variants of COVID-19 are limited. This study will provide an integrated evaluation on efficacy, safety and immunogenicity of COVID-19 vaccines.